1995
DOI: 10.1007/bf00547632
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal bioaccumulation in different tissues of two fish species with regards to their feeding habits and trophic levels

Abstract: Heavy metals residues (i.e. Cu, Zn, Mn, and Pb) were determined in seven chosen tissues of two fish species (Esox lucius and Carassius auratus) from Anzali wetland. The impact of feeding habit on metal accumulations in different tissues as well as the respective contribution of water and food to matel uptake by fishes were considered. No tendency for bioamplification was observed for the metals along the wetland trophic levels. Generally, there was no statistically significant relationship between the metal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 10 publications
5
32
0
1
Order By: Relevance
“…In our study, significant negative correlation was found between concentration of Cu in muscle of P. vachelli and fish length (p \ 0.01), while significant positive correlations were observed between fish length and concentrations for As in liver of C. heterodon, Cu in gill, and Hg in liver of P. vachelli (p \ 0.05). Positive relationships between metal concentrations in fish tissues and length were also reported in other studies (Pourang 1995;Farkas et al 2003). Fish often demonstrate increasing levels of toxicants with size or age, which appears to be consistent with the longer exposure of older animals (Jureša and Blanuša 2003).…”
Section: Resultssupporting
confidence: 60%
“…In our study, significant negative correlation was found between concentration of Cu in muscle of P. vachelli and fish length (p \ 0.01), while significant positive correlations were observed between fish length and concentrations for As in liver of C. heterodon, Cu in gill, and Hg in liver of P. vachelli (p \ 0.05). Positive relationships between metal concentrations in fish tissues and length were also reported in other studies (Pourang 1995;Farkas et al 2003). Fish often demonstrate increasing levels of toxicants with size or age, which appears to be consistent with the longer exposure of older animals (Jureša and Blanuša 2003).…”
Section: Resultssupporting
confidence: 60%
“…Cadmium, mercury, and lead were determined in a dorsal muscle due to their important role in human nutrition and for ensuring the safety of consumers. The liver was analysed as an organ where main metabolism and major injuries take place (Pourang 1995). The obtained results were assessed and compared.…”
mentioning
confidence: 99%
“…Most of fish organs are sensitive against toxicity of metals. In this study, muscle tissues due to their important role in human nutrition and the need to ensure the safety of consumption, gill tissues due to their role in respiration and osmotic balance, and liver due to being a member that main metabolism and major injuries will endure in, were chosen (Pourang 1995). The study showed that the highest concentrations of metals are found in the gill and liver (p [ 0.05), while the lowest concentrations are found in the muscle.…”
Section: Resultsmentioning
confidence: 99%
“…These are non-essential metals due to their toxicity, even in tracing amounts (Fernandes et al 2008). Metals enter fish bodies through body surface, gill or the digestive tract (Pourang 1995). Food may also be an important source of metals accumulation in fishes (Clearwater et al 2000), and potentially lead to bio magnification and increase of pollutants in food chain.…”
mentioning
confidence: 99%